PRIMARY-MULTIPLE TUMORS IN PATIENTS WITH NEOPLASMS OF THYROID GLAND - A. F. Romanchishen; K. V. Vabalaite (Вестник хирургии имени И.И. Грекова)
The authors studied the long-term results of surgical treatment of 949 patients with thyroid carcinoma. The malignant tumors of other organs were revealed in 55 (5,8%) cases during 20 years of follow-up. It was stated that patients with thyroid carcinoma had a higher risk of developing other malignant tumors than in population. A typical background for onset of other neoplasms was a latent hypothyroidism, hyperlipidemia, hypersecretion of gonadotropins, an influence of occupational hazard of chemical nature and hereditary load of oncology.